Sustentabilidade da ideia de património numa sociedade em transformação acelerada de paradigma geral - Jorge, Vítor Oliveira (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
This text aims to reflect critically on the feasibility and relevance of trying to continue developing a consistent heritage policy in a globalized neoliberal society, bearing in mind that, with rare exceptions, we may be looking just at a rhetorical screen that hides the very impossibility, inoperability, or obsolescence of that policy.